PENGARUH PENDAPATAN ASLI DAERAH (PAD), DANA ALOKASI UMUM (DAU), DAN DANA ALOKASI KHUSUS (DAK) TERHADAP ALOKASI BELANJA MODAL (STUDI EMPIRIS PADA KABUPATEN DAN KOTA DI PROVINSI JAWA TIMUR) - Paso, Maria Aurelia Voni; Hariani, Lilik Sri; Mustikawati, Rita Indah (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2017)
This study aims to determine the effect of Local Revenue (PAD), the General Allocation Fund (DAU), and the Special Allocation Fund (DAK) on Capital Expenditure Allocation. Capital expenditure has an important role because it can add fixed assets and provide services to the public. The samples are 29 Regencies and 9 Cities in East Java Province who reported the 2015 Regional Government Budget (APBD) to the Director General of Fiscal Balance and Finance. The analytical tool used is multiple linear regression analysis. The study finds that simultaneous Local Revenue (PAD), the General Allocation Fund (DAU), and Special Allocation Fund (DAK) influence to Capital Expenditures. Partially, Local Revenue (PAD) and the General Allocation Fund (DAU) affect capital expenditure, while Special Allocation Fund (DAK) does not affect to The Capital Expenditure.